Ciência e sabedoria de vida na filosofia transcendental de Kant à luz do estoicismo - Bicalho, Vanessa Brun (2021)
This PhD dissertation aims to investigate, in the light of Stoicism, the concepts of science and life wisdom in the constitution of Kant's transcendental philosophy – especially in its critical phase – from the rescue of affiliations that led Kant to the knowledge of the Stoic philosophers' conception of life and way of thinking. In contrast to rational/scholastic thinking that conceived an excessive emphasis on reason but did not show any authentic degree of importance to the faculty of sensibility, Immanuel Kant carries out one of the most radical reforms in the field of philosophical grounding by operating transcendental philosophy as a method that critically approaches the pure reason, with the intention of instituting the investigation and demarcation of the limits and boundaries between science (ectypa nature) and freedom (archetypal nature), thought by the nucleus of the transcendental subject. It is from the adequate thematization of the grounding of the science of reason on itself and on its possibility that Kant will divide the two domains of reason within philosophy, namely, theoretical reason and practical reason. Only in this way it can lead to transcendental philosophy as a radically critical conception, been able to separate the objects that belong to the metaphysics of nature and those that belong to the metaphysics of customs. The motivation of the Stoics to Kantian transcendental philosophy came, therefore, to support the demand for the grounding of reason in what had already been accomplished, executed, and experienced by ancient Stoic doctrine, namely: the harmonious relationship between science and life wisdom. In this sense, the task of this investigation is to equate the issues about the reform of metaphysics and the moral-practical sense of transcendental reason, which point to the true wisdom of life (perhaps always intuited by philosophical schools, but never truly founded): the symmetry between knowledge and wisdom. In this comparison, it is intended to show that the critical-transcendental perspective of Kantian reason achieves a sui generis relationship between science and life wisdom through the appropriation of the Stoic doctrine of the Highest Good as an element that represents the crowning of the elucidation on the way Kant incorporated the consummation of the union between science (knowledge) and life wisdom (ethics) into his ethical formalist perspective and from the point of view of the practical reason primacy, since true ethics needs knowledge, just as knowledge becomes true only insofar as it does not dispense with authentic ethics.